Fuzzy Frontiers? Testing the Fluidity of National, Partisan and Brexit Identities in the Aftermath of the 2016 Referendum. - Kenny, John; Heath, Anthony; Richards, Lindsay (Political Studies, 2023)
British and English national identities have long been considered to have porous boundaries whereby English individuals consider the terms more or less interchangeable. However, there is no empirical evidence to demonstrate whether primary feelings of either Britishness or Englishness are highly fluid within-individuals or whether individuals are consistent in their perceptions of their British or English identity. This is especially relevant in the post-Brexit referendum context where national identity is highly correlated with Brexit attitudes. Using panel data, we demonstrate that there is a notable degree of fluidity between identifying as British or English. This is higher than the fluidity between other national identities in the UK as well as more fluid than moving between any partisan or EU referendum identities. Remainers are more fluid than Leavers in their Englishness, whereas they are similar in the fluidity of their Britishness.